The P.E.T. comfort index: Questioning the model. (June 2018) - Walther, E.; Goestchel, Q.
Abstract: This work is a first thorough presentation of the widely used PET ( Physiological Equivalent Temperature ) comfort index. It underlines the simplifications made in solving the equation system for the PET and proposes a correction of the errors in the widespread version of the PET calculation routine. A comparison of the corrected model with a stringent solving of the equation system is made: as a result, the PET calculated after the original method introduces a bias of − 0.5 to + 2.3 [K] in the studied conditions (operative temperature, high mean radiant temperature and windy environments). The original vapour diffusion model is also examined and shows no dependency to the clothing level. The comparison with a state-of-the-art vapour transfer model exhibits a significant − 7 to + 2.6 [K] discrepancy with the corrected PET model in the aforementioned studied conditions. Links to the two versions of the code are provided in the appendix. Highlights: First complete description of the PET model. Correction of mistakes and typos in the original code. Proposal of a state-of-the-art diffusion model for latent heat transfer through clothing. Faster and more compact calculation routine provided.